A bibliometric analysis of the theme trends and knowledge structures of pulmonary embolism from 2017 to 2021 - Fan, Jingjing; Xu, Xiaoman; Zhao, Li (Frontiers in Medicine, 2023)
Background Pulmonary embolism (PE) is a popular area of research in the field of respiratory medicine. We performed a bibliometric analysis based on PubMed database to characterize the distribution pattern of literature and knowledge structures related to PE. Methods Literature pertaining to PE from January 1, 2017, to December 31, 2021, was retrieved from the PubMed database. Bibliographic information was generated using the Bibliographic Item Co-Occurrence Matrix Builder (BICOMB). The visualization matrix was established using gCLUTO software. Strategic diagram analysis was performed using GraphPad Prism 9 software. Social network analysis (SNA) was generated using Ucinet6.0 and NetDraw 2.084 software. Results Out of all the retrieved MeSH terms and subheadings, 52 MeSH terms/MeSH subheadings with a high frequency were found, and hot subjects were sorted into 6 clusters. The strategy diagram showed that the epidemiology, etiology, and drug therapy of PE were well advanced. In contrast, studies on diagnostic imaging, pathology, and complications of PE were still immature and offered potential research space. Social network analysis showed that marginal topics such as surgical treatment of pulmonary hypertension, prevention and control of postoperative complications, and metabolism and analysis of fibrin/fibrinogen degradation products were emerging research hotspots. Conclusion Objective analysis of the research developments in the field of PE can provide intuitive knowledge structure for researchers and clinicians. Analysis of the research hotspots related to PE is helpful for researchers and clinicians by highlighting future research directions.